Digitally Decoding Heritage: Analyzing the Sellman Tenant House Through HBIM and Digital Documentation Techniques - Botao Li; Danielle S. Willkens; Shadi Alathamneh; Sharon C. Park; Junshan Liu (Virtual Worlds)
This study presents a comprehensive digital documentation and preservation effort for the Sellman Tenant House, a historic structure once part of the 18th-century Sellman Plantation in Maryland, USA. This research employs an array of digital technologies, including Terrestrial Laser Scanning (TLS), digital photogrammetry, Unmanned Aerial Vehicles (UAVs), 3D virtual tours, and Heritage Building Information Modeling (HBIM), to document and analyze the construction techniques and historical evolution of the house. Given the absence of written records detailing its original construction, this study utilizes data from these digital documentation methods to explore the building’s structure and determine its construction timeline and methods. Additionally, this research investigates the potential of HBIM as an educational platform to enhance public understanding of heritage buildings by creating interactive and accessible digital models. The findings highlight the effectiveness of combining digital tools to decode vernacular construction and showcase the potential of HBIM in preserving and interpreting historic buildings for diverse audiences, especially for educational purposes. This research contributes to the growing field of digital heritage preservation by showcasing a case study of integrating multiple digital technologies to study, preserve, and promote understanding of a culturally significant yet understudied structure.